if f(x)=(x^2)(e^x) prove by induction that the nth derivative is (x^2 +2nx +n(n-1)(e^x)

thanks

step 1.

test if it is true for n=1
1st deriv
= x^2e^x + 2xe^x
= e^x(x^2 + 2x)

by your formula is should be
e^x(x^2 + 2(1)x + 1(0))
= e^x(x^2 + 2x) check!

(I also tested it for n=2 and 3, and it checked

step 2. assume true for n=k
i.e.
kth deriv
= e^x(x^2 + 2kx + k(k-1))

step 3.
then (k+1)th deriv should be
e^x(x^2 + 2(k+1)x + (k+1)(k))

so let's differentiate the kth deriv

(k+1)th deriv
= e^x(2x + 2k) + (x^2 + 2kx + k(k-1))e^x
= e^x[x^2 + 2kx + 2x + k(k-1) + 2k]
= e^x[x^2 + 2x(k+1) + k^2 + k]
= e^x[x^2 + 2(k+1)x + k(k+1)]

as required

Q.E.D.

To prove by induction that the nth derivative of f(x) = x^2 * e^x is (x^2 + 2nx + n(n-1) * e^x), we will follow these steps:

Step 1: Base Case
First, we need to prove the statement for the base case (n = 1).
The first derivative of f(x) with respect to x is given by:
f'(x) = d/dx(x^2 * e^x)

Using the product rule, we can differentiate f(x) with respect to x:
f'(x) = 2x * e^x + x^2 * e^x

This matches (x^2 + 2x + 1*(1-1) * e^x) as n = 1, so the base case is true.

Step 2: Inductive Hypothesis
Assume the statement is true for the nth derivative, i.e., the nth derivative of f(x) is given by:
f^n(x) = (x^2 + 2nx + n(n-1) * e^x) ----(1)

Step 3: Inductive Step
We need to prove that the statement is true for (n+1)th derivative, i.e., the (n+1)th derivative of f(x) is given by:
f^(n+1)(x) = (x^2 + 2(n+1)x + (n+1)(n)((n+1)-1) * e^x) ----(2)

To do this, we differentiate Equation (1) with respect to x:

f^n(x) = (x^2 + 2nx + n(n-1) * e^x)

Differentiating both sides with respect to x gives:
f^(n+1)(x) = d/dx[(x^2 + 2nx + n(n-1) * e^x)]

Differentiating each term using the product rule and simplifying the expression, we get:
f^(n+1)(x) = (2x + 2n + 2n(n-1) + n(n-1)) * e^x + (x^2 + 2nx + n(n-1)) * e^x
f^(n+1)(x) = (x^2 + 2(n+1)x + (n+1)(n)((n+1)-1) * e^x)

This matches Equation (2), and thus the statement is true for (n+1).
Hence, the statement is proven by induction.

To prove this statement by induction, we need to first establish the base case and then prove the inductive step.

Step 1: Base Case
Let's start by proving the statement for n = 1, which is the base case.

Given f(x) = (x^2)(e^x), we need to find the first derivative, f'(x).

f'(x) = d/dx[(x^2)(e^x)]

Using the product rule, we can differentiate this function:

f'(x) = (d/dx)(x^2)(e^x) + (x^2)(d/dx)(e^x)

Simplifying this expression:

f'(x) = 2x(e^x) + (x^2)(e^x)

This matches the expression for n = 1: (x^2 + 2x + e^x). Thus, the base case holds true.

Step 2: Inductive Step
Now, let's assume that the statement is true for n = k, i.e., the kth derivative of f(x) is given by:

f^(k)(x) = (x^2 + 2kx + k(k-1))(e^x)

We need to prove that the statement holds true for n = k+1, i.e., we need to show that the (k+1)th derivative of f(x) is given by:

f^(k+1)(x) = (x^2 + 2(k+1)x + (k+1)(k)(e^x)

To do this, we'll differentiate the assumed expression for n = k.

f^(k+1)(x) = (d/dx)[(x^2 + 2kx + k(k-1))(e^x)]

Using the product rule and the assumption, we can simplify this expression:

f^(k+1)(x) = 2k(e^x) + (x^2 + 2kx + k(k-1))(e^x) + (x^2 + 2kx + k(k-1))(e^x)

Simplifying further:

f^(k+1)(x) = (2k + 2)(e^x) + (2k + 1)(x^2 + 2kx + k(k-1))(e^x)

Expanding the quadratic term:

f^(k+1)(x) = (2k + 2)(e^x) + (2k + 1)(x^2 + 2kx + k^2 - k)(e^x)

Rearranging and combining like terms:

f^(k+1)(x) = (x^2 + 2(k+1)x + (k+1)k)(e^x)

This matches the expression for n = k+1. Therefore, the statement holds for n = k+1.

Step 3: Conclusion
Since we have proven that the statement is true for the base case (n = 1) and have shown that if it holds for n = k, it also holds for n = k+1, we can conclude that the statement is true for all positive integers n by mathematical induction.